The Business Mindset of The Tourism Village Community Organizations: Value and Supply Chain Analysis - Sumardi, Valentino; Sopian, Tatang; Rosadi, Asep; Hutahaean, Renalmon (Journal of Mandalika Review, 2025)
Introduction: This article delves into the intricate dynamics of the tourism village community organizations, elucidating the essential role of a business mindset in navigating the complexities of the tourism industry. As a new tourism village, Neglasari village was designated as one of the pioneer tourism villages of the Southern part of Garut Regency in 2021. Followed by the formation of two village community organizations namely the village-owned enterprise (Bumdes Bangun Jaya) and the tourism awareness group (Pokdarwis Neglasari) in 2023. Some of potential tourist attractions among others Jagapati Waterfall and Puncak Lendra Tea Plantation.Methodology: This qualitative research used focus group discussions technique explore and collect the data from all members of the community organizations, Pokdarwis Neglasari and Bumdes Bangun Jaya.Findings: The village community organizations have passions for solving problems and willingness to accept changes. The business mindset of Pokdarwis Neglasari and Bumdes Bangun Jaya revolves around community empowerment, collaboration, sustainable practices, and continuous improvement through value chain analysis. By leveraging their cultural and natural assets, these organizations not only enhance the tourism experience but also foster socio-economic development within their communities.Conclusion: Based on the tourism value chain, that tourist village have uniqueness that is the basis for the development of tourism village products, and based on tourism supply chain, their high collaboration with suppliers improves the quality of their products and provides advantages to enhance their competitive position in the market.